2009
DOI: 10.1007/s11356-009-0191-8
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and temporal variations of TMDD in the river Rhine, Germany

Abstract: Background, aim, and scopeThe chemical substance 2,4,7,9-tetramethyl-5-decyne-4,7-diol (TMDD) is a non-ionic surfactant used as an industrial defoaming agent and in various other applications. Its commercial name is Surynol 104® and the related ethoxylates are also available as Surfynol® 420, 440, 465 and 485 which are characterized by different grades of ethoxylation of TMDD at both hydroxyl functional groups. TMDD and its ethoxylates offer several advantages in waterborne industrial applications in coatings,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 19 publications
2
11
0
1
Order By: Relevance
“…On the other hand, TMDD was quantified in 25% of the samples with a median concentration of 347 ng/L. This compound has so far been investigated in only 2 studies [18,28], and reported at mean concentrations of about 500 ng/L, which is in accordance with our study. Finally, anionic surfactants were the most frequently quantified, and at the highest concentrations, especially LAS.…”
Section: Application To Field Samplessupporting
confidence: 92%
See 1 more Smart Citation
“…On the other hand, TMDD was quantified in 25% of the samples with a median concentration of 347 ng/L. This compound has so far been investigated in only 2 studies [18,28], and reported at mean concentrations of about 500 ng/L, which is in accordance with our study. Finally, anionic surfactants were the most frequently quantified, and at the highest concentrations, especially LAS.…”
Section: Application To Field Samplessupporting
confidence: 92%
“…They generally focused on only one type of surfactant, anionic [6,[10][11][12][13], cationic [8,14] or non-ionic [15][16][17][18]. Very few analytical methods were developed and validated for more than one type of surfactant.…”
Section: Introductionmentioning
confidence: 99%
“…TMDD concentrations as high as 3300 g L −1 were detected in effluents of paper-recycling and printing ink producing facilities, and industrial inputs are the main source of river contamination with TMDD [18]. TMDD has been previously detected in German rivers [19,20] and has a low elimination rate during wastewater treatment that ranges from 33 to 68% [21].…”
Section: Specific Organic Contaminants Related To Paper Productionmentioning
confidence: 99%
“…TMDD has been recently discussed in detail as river water contaminant (Guedez et al 2009). However, the knowledge of this environmentally stable high-production volume chemical as surface water pollutant is still restricted (e.g., Hankemeier et al 1999;Kronimus et al 2006;Loraine and Pettigrove 2006).…”
Section: Potential Contributions To Large-scale Monitoring Programsmentioning
confidence: 99%